How Urban Forest Managers Evaluate Management and Governance Challenges in Their Decision-Making - Camilo Ordóñez (Forests, 2020)
Decisions about urban forests are critical to urban liveability and resilience. This study aimed to evaluate the range of positions held by urban forest managers from local governments in the state of Victoria, Australia, regarding the management and governance challenges that affect their decision-making. This study was based on a Q-method approach, a procedure that allows researchers to evaluate the range of positions that exist about a topic in a structured manner based on the experiences of a wide group of people. We created statements on a wide range of urban forest management and governance challenges and asked urban forest managers to rate their level of agreement with these statements via an online survey. Managers generally agreed about the challenges posed by urban development and climate change for implementing local government policies on urban forest protection and expansion. However, there were divergent views about how effective solutions based on increasing operational capacities, such as increasing budgets and personnel, could address these challenges. For some managers, it was more effective to improve critical governance challenges, such as inter-departmental and inter-municipal coordination, community engagement, and addressing the culture of risk aversion in local governments. Urban forest regional strategies aimed at coordinating management and governance issues across cities should build on existing consensus on development and environmental threats and address critical management and governance issues not solely related to local government operational capacity.